Determinants of Investment Decisions among Retirables: Towards an Investment Planning Model - Lovely Tinguha; Romario Ybanez (Philippine Association of Institutions for Research, Inc., 2023)
This study is about the determinants of investment decisions among retirables to evaluate their preparedness of retirables in terms of investment before they retire, the perceived factors that influence them to invest, and their knowledge and education in financial management. It also creates an investment planning model that will fit the needs of the individual depending on their income and risk appetite to invest. The study uses a descriptive correlational method, and the results revealed no significant difference between the respondents according to the three determinants (Investment Behavior, Financial Preparedness, and Investment Influencers). Therefore, they do not differ in terms of determinants in making decisions. However, there was a significant relationship between investment determinants of retirables and investment influencers. The correlation of 0.864 between investment determinants and investment influencers for the retirables was highly correlated and statistically significant. The investment determinants influence investment decision-making; thus, it is claimed that determinant factors are extremely important to implement their investment plan for retirement preparedness. Consequently, knowing the investment determinant behavior is the key to practicing Investment planning. It is recommended, therefore, to strengthen the level of financial preparedness and education of employed people at an early age to raise awareness and improve their understanding of financial risks when they are no longer earning (retired) and make necessary investments.